2016
DOI: 10.1172/jci84440
|View full text |Cite
|
Sign up to set email alerts
|

LYN- and AIRE-mediated tolerance checkpoint defects synergize to trigger organ-specific autoimmunity

Abstract: Studies of the genetic factors associated with human autoimmune disease suggest a multigenic origin of susceptibility; however, how these factors interact and through which tolerance pathways they operate generally remain to be defined. One key checkpoint occurs through the activity of the autoimmune regulator AIRE, which promotes central T cell tolerance. Recent reports have described a variety of dominant-negative AIRE mutations that likely contribute to human autoimmunity to a greater extent than previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…Aire and the inhibitory protein tyrosine kinase Lyn, which developed autoimmune uveitis, underscoring the cooperation between central and peripheral tolerance checkpoints in the organ-specific phenotypic expression of autoimmune disease 129. Similarly, mice with deficiency in both Aire and the T cell peripheral tolerance checkpoint Cbl-b (Casitas B-lineage lymphoma), which modulates CD28 co-stimulation, developed lethal exocrine pancreatic autoimmune disease 130.…”
mentioning
confidence: 99%
“…Aire and the inhibitory protein tyrosine kinase Lyn, which developed autoimmune uveitis, underscoring the cooperation between central and peripheral tolerance checkpoints in the organ-specific phenotypic expression of autoimmune disease 129. Similarly, mice with deficiency in both Aire and the T cell peripheral tolerance checkpoint Cbl-b (Casitas B-lineage lymphoma), which modulates CD28 co-stimulation, developed lethal exocrine pancreatic autoimmune disease 130.…”
mentioning
confidence: 99%
“…Using a short-term course of the same antibiotic mix, disease in the immunization-induced model was temporarily ameliorated, which the authors felt could be attributed at least in part by emergence of T regulatory cells in the intestine of antibiotic-treated mice, possibly as a result of the altered microflora. In contrast, broad-spectrum antibiotics did not affect progression of spontaneous uveitis in a recent report using the model of combined mutations in hypomorphic AIRE function and LYN deficiency [15]. The length of antibiotic treatment that was used in different studies (weeks vs. months) and/or the specific microbial environments in various facilities may underlie these differences.…”
Section: Animal Studies On Microbiota and Uveitismentioning
confidence: 99%
“…More recently, Proekt et al (15) reported that a dominant-negative AIRE allele (G228W point mutation), with only partial penetrance, resulted in high incidence of uveitis when combined with LYN-deficiency (which by itself leads to a lupus-like disease). The findings support the notion of multiple gene defects combining for an overtly autoimmune phenotype.…”
Section: A Spontaneous Autoimmune Uveitis Model In Which Commensal MImentioning
confidence: 99%